Sociology of Development - Kuhn, Randall (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
This course provides a survey of issues relating to national, community, and human development in Less Developed Countries (LDCs). We will focus on understanding the complex role of individuals, families, communities, and the state in determining social and economic outcomes within the LDC context. In addition to providing a general understanding of the levels of analysis relevant to the Sociology of Development, the material will, at times, focus on specific issues such as inequality, risk, poverty, migration, gender, famine, and the environment. We close the course by looking beyond the technical and theoretical aspects of development to address the meaning and importance of development as a goal in itself, and the role of identity and agency in the study of development.